(untitled) (Revista de Medicina Clinica, 2020)
BACKGROUND: Otosclerosis is a condition that causes hearing loss, after chronically infected ear surgery, corresponds to the second cause of otological surgery in our region, surgery with Teflon prosthesis placement is well established, with success rates is high , with low complications. OBJECTIVE: To determine the audiological results of the surgical treatment of otosclerosis in the two techniques performed in a third level of care. Â MATERIAL AND METHODS: The records of patients operated for stapedectomy and stapedotomy for otosclerosis from January 2017 to November 30, 2019 in our service were reviewed. Data such as age, sex, signs and symptoms, pre and post-surgical audiological data were taken. We use Chi2 to evaluate the dichotomous categorical variables, the qualitative, nominal and ordinal variables, were interpreted by means of the calculation percentage, proportion, rate or relation. SPSS version 22.0 was used RESULTS: Of 50 intervened ears, 44% underwent stapedectomy and 56% stapedotomy. The improvement in the average pure tone of the air-bone space (GAP) was 27.8 dB for stapedectomy and 31.5 dB for stapedotomy. No significant relationship was found between the success of the surgery and the type of procedure. (p 0 .2436). The success rate was 86%. CONCLUSION: No significant relationship was found between the success of the surgery and the type of procedure used. The success rate in our patients is similar to that reported in other international hospital centers.